MSMEs Waste Pineapple Natural Dyes Jumputan Fabric Local Wisdom Outskirts of the Era Covid-19 - lesi* lesi; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Universitas Nahdlatul Ulama Lampung, 2021)
The process of making Jumputan cloth is unique. Jumputan is a handicraft made by picking (picking up with your fingers) certain parts of the cloth, then producing a pattern according to the pattern drawn from the process of dyeing natural dyes or textile dyes from tightly tied fabric tied pineapple waste which is useless for use by indigenous peoples As a natural dye to make the color of the cloth used, Pineapple waste is often thrown away immediately. In fact, if it is used as an interesting work, it will benefit the wider community. By making Pineapple waste a beautiful work of art, the price is high. Many people are interested in having it. In addition to being useful again, the results of used Pineapple Limah handicraft products can be a business opportunity. Pineapple is usually made as simple as food to eat with bread, this time pineapple waste is a light and easy to use material, even by using and playing with pineapple waste it can produce interesting works of expensive Jumputan. Not a few people still think that pineapples have a fragile character and are easily rotten, especially not for long, this time it is used for natural dyes for jumputan fabrics.